Identifying pre_remarriage educational needs: A grounded theory study - Maryam Rezaei; Esmaeil Asadpour; Farshad Mohsenzade; Kianoush Zahrakar (مجله علوم روانشناختی, 2022)
Background: Remarriage is a new opportunity to experience married life, but the theoretical and experimental backgrounds in this field indicate that this group experiences a lot of psychological, communication, and family stress. Also, the divorce rate is high among them. However, this group’s perceptual challenges and educational needs have not been comprehensively identified in specific research, and there is a research gap in this regard. Aims: This study aimed to identify pre-marital educational needs. Methods: The research was qualitative and grounded theory. The researcher selected men and women with experience of remarriage in Tehran. For this purpose, 16 men and women (identified by virtual call) and 12 professionals (identified by marriage and family association) were selected by purposive sampling. Interviews were recorded and analyzed using Strauss and Corbin (1998). Results: The analysis of the interviewees’ statements led to the design of a remarriage readiness model, with one primary theme (realistic selection and secure entry into a challenging relationship), four causal factors (clarification of remarriage criteria, analysis of individual readiness, having knowledge to find the appropriate match, and examining the possibility of unhealthy reasons for remarriage), three underlying factors (awareness of the role of family barriers, insight into marital and parenting challenges), four interfering factors (facilitating the release of the individual from the previous relationship, strengthening intrapersonal capabilities, strengthening marital skills and teaching communication requirements in interaction with children), four actions (participatory solution of challenges related to children, accepting the couple’s challenges and participating in addressing, defining the parent-child relationship based on affection, and defining marital relationship based on love) and a consequence (quality remarried life). Conclusion: The research results provided the basis for designing pre-remarriage education programs that increase the likelihood of a quality remarriage.